The cave 4 Apocryphon of Jeremiah and the Qumran Jeremianic traditions: prophetic persona and the construction of community identity - Davis, Kipp (Studies on the texts of the desert of Judah, 2014)
The Cave 4 'Apocryphon of Jeremiah C' from Qumran survives in several copies, and presents significant links between the prophet Jeremiah, the scriptural book of Jeremiah, and the collectors of the Dead Sea Scrolls. Because the prophet is only occasionally named in the Scrolls, and there are only a few clear instances where the book is cited, Jeremiah appears to have had a limited impact on the imagination of the Qumranites. However, through a careful appraisal of the Apocryphon manuscripts, and a reconsideration of Jeremiah's influence in the Dead Sea Scrolls via his reputational authority, this study shows that clusters of traditions were tied to Jeremiah's prophetic and priestly distinction, with an emphasis on matters of leadership and empire